Some New Capital Budgeting Theorems: Comment - Bernhard, Richard H. (Journal of Financial and Quantitative Analysis, 1978)
In this issue of the Journal of Financial and Quantitative Analysis, Beranek [2] has presented a clever but cumbersome analysis showing that, for a simple multiperiod situation, computing a project's net present worth by discounting its cash flows at particular “costs of capital” and accepting the project if that net present worth is positive is completely consistent with raising the net present wealth of stockholders, initial investment from whom provides partial funding for the project.